Pengaruh Kecerdasan Emosional Dan Sikap Terhadap Organizational Citizenship Behaviour Karyawan Pt Toyota Agung Automall Bengkulu - Rendy Alpahrasy; Sigit Nugroho; Trisna Murni (Universitas Bengkulu, 2021)
The purpose of this study is aimed to know how influence of emotional intelligence and attitude on employee?s performance of PT Toyota Agung Automall Bengkulu. The subject of this study are employee who have worked on PT Toyota Agung Automall Bengkulu. Data were collected via questionnaires and questionnaire was distributed directly to respondents, namely by giving questionnaires directly to employee of PT Toyota Agung Automall Bengkulu, while respondent amount 84 effective samples were collected to verify the hypotheses of this study. For data analysis and hypotheses testing, multiple linier regresion techique was used. Sampling techinique in this study using census method where census method used data collection is done by investigating one by one the entire population. Pursuant of data analysis obtained results that is emotional intelligence have a positive and significantly effect on organizational citizenship behaviour of employee and attitude have significantly effect on organizational citizenship behaviour of employee.